2012
DOI: 10.1111/j.1365-3091.2012.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

An interglacial on snowball Earth? Dynamic ice behaviour revealed in the Chuos Formation, Namibia

Abstract: The Sturtian is the oldest (ca 716Ma) of three pan-global glaciations in the Cryogenian. At Omutirapo, in northern Namibia, a 2km wide, 400m deep palaeovalley is filled by glaciogenic strata of the Chuos Formation, which represents the Sturtian glacial record. Sedimentary logging of an exceptionally high-quality exposure permits detailed stratigraphic descriptions and interpretations, allowing two glacial cycles to be identified. At the base of the exposed succession, strong evidence supporting glaciation incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Syvitski & Hein, ; Hansen, ; Fraser et al ., ; Corner, ; Eilertsen et al ., ; Nutz et al ., , ; Normandeau et al ., ) and in the deep time glacial record (e.g. Proust & Deynoux, ; Ghienne, ; Le Heron et al ., , , ; Isbell et al ., ; Loi et al ., ; Girard et al ., ). The nature and mode of deposition of such deglacial sedimentary sequences are controlled by complex interactions between the history of ice margin retreat (for example, slow, punctuated, rapid retreat) and evolution of the related sediment entry points, the inherited basin physiography and paraglacial reworking processes, among others (Syvitski & Farrow, ; Brookfield & Martini, ; Lønne et al ., ; Powell & Cooper, ; Lajeunesse & Allard, ; Occhietti, ; Storms et al ., ; Hein et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Syvitski & Hein, ; Hansen, ; Fraser et al ., ; Corner, ; Eilertsen et al ., ; Nutz et al ., , ; Normandeau et al ., ) and in the deep time glacial record (e.g. Proust & Deynoux, ; Ghienne, ; Le Heron et al ., , , ; Isbell et al ., ; Loi et al ., ; Girard et al ., ). The nature and mode of deposition of such deglacial sedimentary sequences are controlled by complex interactions between the history of ice margin retreat (for example, slow, punctuated, rapid retreat) and evolution of the related sediment entry points, the inherited basin physiography and paraglacial reworking processes, among others (Syvitski & Farrow, ; Brookfield & Martini, ; Lønne et al ., ; Powell & Cooper, ; Lajeunesse & Allard, ; Occhietti, ; Storms et al ., ; Hein et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Both early and late Cryogenian glaciations, referred to as the Sturtian and Marinoan (based on locations in South Australia), respectively, appear to be globally distributed (Li et al, 2013). In some regions, the history of one or both glaciations is locally or regionally complex, with distinct glacial retreat intervals recognized in South Australia (Williams et al, 2008, Le Heron et al, 2011Rose et al, 2013), Namibia (Hoffman, 2011;Le Heron et al, 2013), Scotland (Spencer, 1971;Arnaud and Fairchild, 2011) and Oman (Leather et al, 2002;Rieu et al, 2007a). However, semi-continuous Cryogenian successions display a clear stratigraphic motif in which two glacial units bound an unambiguously non-glacial interval, representing a mid-Cryogenian interlude of unknown duration (~5-27 My; Rooney et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al . () argued from palaeomagnetic evidence, and entirely counter to the geological record, that Neoproterozoic glacially‐influenced deposits accumulated on ‘stable platforms’, others have suggested that globally‐correlative, orbitally‐forced ice advance and retreat cycles might ultimately be identified from such deposits (Condon et al ., ; Leather et al ., ; Arnaud, ; Rieu et al ., ; Hu et al ., ; Le Heron et al ., ; Benn et al ., ; Busfield & Le Heron, ; Spence et al ., ). These latter ideas are worthy of further investigation but need to be reconciled with what is known of the very active tectonic setting of many Neoproterozoic glacially‐influenced basin fills, which are overwhelmingly deep water mass flow dominated and rift‐related (Western North America, Greenland, Scotland and Scandinavia; Eyles & Januszczak, , ).…”
Section: Discussionmentioning
confidence: 99%